2020
DOI: 10.4049/jimmunol.1901350
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for the CXCL3/CXCL5/CXCR2 Neutrophilic Chemotactic Axis in the Regulation of Type 2 Responses in a Model of Rhinoviral-Induced Asthma Exacerbation

Abstract: Rhinovirus (RV) infections in asthmatic patients are often associated with asthma exacerbation, characterized by worsened airways hyperreactivity and increased immune cell infiltration to the airways. The C-X-C chemokines, CXCL3 and CXCL5, regulate neutrophil trafficking to the lung via CXCR2, and their expression in the asthmatic lung is associated with steroid-insensitive type 2 inflammatory signatures. Currently, the role of CXCL3 and CXCL5 in regulating neutrophilic and type 2 responses in viral-induced as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…RV infection and replication in epithelial cells activate innate immune responses and induce expression of growth factors and chemokines, which leads to recruitment and activation of granulocytes, including neutrophils, destruction of normal airway tissue, and development of respiratory symptoms. 13,15,16 MicroRNAs (miRNAs) are short non-coding RNAs that modulate various biological processes through posttranscriptional regulation of gene expression. 17 More specifically, miRNAs recognize and bind to the 3′ untranslated regions (3′UTRs) of multiple target mRNAs via the complementarity of 6-to 8-nt-long seed regions present in miR-NAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RV infection and replication in epithelial cells activate innate immune responses and induce expression of growth factors and chemokines, which leads to recruitment and activation of granulocytes, including neutrophils, destruction of normal airway tissue, and development of respiratory symptoms. 13,15,16 MicroRNAs (miRNAs) are short non-coding RNAs that modulate various biological processes through posttranscriptional regulation of gene expression. 17 More specifically, miRNAs recognize and bind to the 3′ untranslated regions (3′UTRs) of multiple target mRNAs via the complementarity of 6-to 8-nt-long seed regions present in miR-NAs.…”
Section: Introductionmentioning
confidence: 99%
“…From the minor group, RV‐A1b has often been used in research. RV infection and replication in epithelial cells activate innate immune responses and induce expression of growth factors and chemokines, which leads to recruitment and activation of granulocytes, including neutrophils, destruction of normal airway tissue, and development of respiratory symptoms 13,15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils require Cxcl2 for more neutrophils recruitment ( 41 ). Inhibition of Cxcl3 in a mouse model of RV-induced exacerbation of asthma decreased the accumulation of Cxcr2 + neutrophils ( 42 ). Cxcl10-Cxcr3 acts in an autocrine way on the oxidative burst and chemotaxis in the inflamed neutrophils ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the common cold virus, hRV is the most prevalent pathogen to circulate constantly in the human community, and it is known to be the most important trigger of asthma exacerbations ( 3 4 5 6 ). Even though murine models infected with minor or major groups of hRV have been used to depict several mechanisms that could explain asthma exacerbations ( 39 57 58 ), a better understanding of personal and environmental risk factors and inflammatory mechanisms is needed to develop new strategies that can prevent and treat asthma exacerbations. In this study, we have demonstrated that IDO is required to prevent neutrophilic airway inflammation during asthma exacerbations caused by hRV infection.…”
Section: Discussionmentioning
confidence: 99%